NEPHROTIC SYNDROME: MINIMAL CHANGE DISEASE - AZIZ, FARIDA; QURESHI, AZHAR MUNIR (Journal of Ayub Medical College Abbottabad, 2001)
Heavy Proteinuria. Edema. Hyperproteinemia. and Hyperlipidemia characterize the nephrotic syndrome (NS). CLASSIFICATION The syndrome can be divided into congenital, primary (idiopathic), and secondary types. 1. Minimal-change disease. (75%) 2. Mesangio- proliferative. (<5%) 3. Focal-segmental lesion. (10%) 4. Membranous nephropathy. (<5%) 5. Membrano proliferative glomerulonephritis. Type I, II and III (10%). ETIOLOGY 90% of the children have some form of the idiopathic nephrotic syndrome. Minimal-change disease is found in approximately 75%. Where as in 10% of the children with Nephrosis, the nephrotic syndrome is largely mediated by some form of glomerulonephritis, membranous and Membrano-proliferative are most common. It is widely accepted that minimal change nephrotic syndrome (MCNS) is the most common cause of nephritis in children. Recent studies show that the incidence of Focal Segmental Glomerulosclerosis (FSGS) in children with idiopathic nephrotic syndrome has increased recently.29